I ncidence des variations p récoces de l’intervalle « QT » induit e s sous t raitement m édical o ncologique dans la région de Djelfa et de Laghouat : étude rétro prospective dans les services d’oncologie du CAC de D jelfa , de l’EPH KEH et de l’hôpital mixte de Djelfa - SAIDI Aya.; BENTAHAR Nihal.; ABDELALI Hadjer. (université ammar telidji laghouat, 2025)
Although oncological medical treatment is effective against many cancers, it can lead to cardiovascular side effects, notably alterations in ventricular repolarization. Among these, QT interval prolongation is a potentially serious complication that may progress to malignant arrhythmias such as torsades de pointes. This study focuses on the variation of the QT interval in patients undergoing chemotherapy, with early rhythm disorders as a secondary objective. It is a retro-prospective, observational, and descriptive study conducted in the oncology departments of the following institutions : the CAC of Djelfa, the Mixed Hospital of Djelfa, and the EPH of KEH. The study includes 170 patients undergoing oncological medical treatment over a 6-month period, from May 2024 to November 2024. Data collection will be carried out through patient interviews, hospitalization records, and three ECGs (before / during / after chemotherapy) to detect possible asymptomatic cardiac rhythm disturbances. Global cardiovascular risk stratification will be performed using the ESC CVD Risk Calculation application. An individual data collection sheet is used to gather various parameters for improved analysis. For each patient, the following data were recorded: name and surname, sex, age, blood pressure, cardiovascular risk factors (hypertension, diabetes, smoking, dyslipidemia, BMI), CV risk score, type of neoplasia, presence and location of metastases, chemotherapy protocol, biological workup (CBC, electrolyte panel, renal function with clearance calculation), ejection fraction (EF), E/A ratio, and HFA-ICOS score. Inclusion criteria included all adult cancer patients undergoing oncological medical treatment. The primary objective of our study was to identify variations in the QT interval induced by oncological medical treatments and the associated risk factors. Among the 170 cases studied, there were 49 men (29%) and 121 women (71%), with a sex ratio of 0.4. The age range was between 19 and 84 years, with a mean age of 52.13 years. Breast cancer was the most frequent type in our series, accounting for 53% (90 patients). Furthermore, 23 cases of QT interval prolongation were identified (22 patients had a QT delta greater than 50 ms, five of them had a corrected QT \[QTc] greater than 500 ms with a delta QTc over 50 ms, and one female patient had a QTc greater than 500 ms alone). Additionally, 10 cases of rhythm disorders were found: five were sinus bradycardia, one atrial premature beat (APB), one atrioventricular block (AVB), one sinoatrial block (SAB), one ventricular premature beat (VPB), and one U wave associated with an APB. A new predictive factor for the occurrence of arrhythmias was identified: a significant QT delta. These results demonstrate a significant variation in the QT interval in some patients, especially in the presence of pre-existing cardiovascular risk factors. A protective trend associated with the use of beta-blockers (BB) was observed, suggesting a potential preventive role against QT prolongation. These findings highlight the importance of rigorous electrocardiographic monitoring in patients undergoing oncological treatment to prevent severe rhythm complications. Thus, close collaboration between oncologists and cardiologists is essential throughout patient management, in accordance with the prevention protocol established by the 2022 ESC guidelines based on risk stratification. Key words : cardiotoxicity ; Oncological medical treatment ; cardiac arrhythmias ; QT prolongation ; risk factors.
CD-ROM